Efavirenz Pharmacokinetics and Pharmacodynamics in HIV-Infected Persons Receiving Rifapentine and Isoniazid for Tuberculosis Prevention - Anthony T. Podany (2018)
© The Author 2015. Background. Concomitant use of rifamycins to treat or prevent tuberculosis can result in subtherapeutic concentrations of antiretroviral drugs. We studied the interaction of efavirenz with daily rifapentine and isoniazid in human immunodeficiency virus (HIV)-infected individuals receiving a 4-week regimen to prevent tuberculosis. Methods. Participants receiving daily rifapentine and isoniazid with efavirenz had pharmacokinetic evaluations at baseline and weeks 2 and 4 of concomitant therapy. Efavirenz apparent oral clearance was estimated and the geometric mean ratio (GMR) of values before and during rifapentine and isoniazid was calculated. HIV type 1 (HIV-1) RNA was measured at baseline and week 8. Results. Eighty-seven participants were evaluable: 54% were female, and the median age was 35 years (interquartile range [IQR], 29-44 years). Numbers of participants with efavirenz concentrations ?1 mg/L were 85 (98%) at week 0; 81 (93%) at week 2; 78 (90%) at week 4; and 75 (86%) at weeks 2 and 4. Median efavirenz apparent oral clearance was 9.3 L/hour (IQR, 6.42-13.22 L/hour) at baseline and 9.8 L/hour (IQR, 7.04-15.59 L/hour) during rifapentine/isoniazid treatment (GMR, 1.04 [90% confidence interval,. 97-1.13] ). Seventy-nine of 85 (93%) participants had undetectable HIV-1 RNA ( < 40 copies/mL) at entry; 71 of 75 (95%) participants had undetectable HIV-1 RNA at week 8. Two participants with undetectable HIV-1 RNA at study entry were detectable (43 and 47 copies/mL) at week 8. Conclusions. The proportion of participants with midinterval efavirenz concentrations ?1 mg/L did not cross below the prespecified threshold of > 80%, and virologic suppression was maintained. Four weeks of daily rifapentine plus isoniazid can be coadministered with efavirenz without clinically meaningful reductions in efavirenz mid-dosing concentrations or virologic suppression.